ENHANCED ACTIVITY OF AN ANGIOTENSIN-(1-7) NEUROPEPTIDASE IN GLUCOCORTICOID-INDUCED FETAL PROGRAMMING - Marshall, Allyson C. (2013)
We previously identified angiotensin converting enzyme (ACE) and an endopeptidase activity that degraded angiotensin-(1-7) [Ang-(1-7)] to Ang-(1-5) and Ang-(1-4), respectively, in the cerebrospinal fluid (CSF) of 6-month old male sheep. The present study undertook a more comprehensive analysis of the CSF peptidase that converts Ang-(1-7) to Ang-(1-4) in control and in utero betamethasone exposed sheep (BMX). Characterization of the Ang-(1-7) peptidase revealed that the thiol agents 4-aminophenylmercuric acetate (APMA) and p-chloromercuribenzoic acid (PCMB), as well as the metallo-chelators o-phenanthroline and EDTA essentially abolished the enzyme activity. Additional inhibitors for serine, aspartyl, and cysteine proteases, as well as selective inhibitors against the endopeptidases neprilysin, neurolysin, prolyl and thimet oligopeptidases did not attenuate enzymatic activity. Competition studies against the peptidase revealed similar IC(50)'s for Ang-(1-7)(5 μM) and Ang II (3 μM), but lower values for Ala(1)-Ang-(1-7) and Ang-(2-7) of 1.8 and 2.0 μM, respectively. In contrast, bradykinin exhibited a 6-fold higher IC(50) (32 μM) than Ang-(1-7) while neurotensin was a poor competitor. Mean arterial pressure (78 ± 1 vs. 94 ± 2 mmHg, N= 4-5, P<0.01) and Ang-(1-7) peptidase activity (14.2 ± 1 vs 32 ± 1.5 fmol/min/ml CSF, N = 5, P<0.01) were higher in the BMX group, and enzyme activity inversely correlated with Ang-(1-7) content in CSF. Lower Ang-(1-7) expression in brain is linked to baroreflex impairment in hypertension and aging, thus, increased activity of an Ang-(1-7) peptidase may contribute to lower CSF Ang-(1-7) levels, elevated blood pressure and impaired reflex function in this model of fetal programming.